Distinct changes of brain cortical thickness relate to post-treatment outcomes in children with epilepsy. (October 2021) - Zhang, Wenjing; Yu, Tao; Liao, Yi; Liu, Sai; Xu, Mengyuan; Yang, Chengmin; Lui, Su; Ning, Gang; Qu, Haibo
Highlights: Two discrete patterns of cortical thickness were identified in children with epilepsy. The distinct changes of cortical thickness relate to post-treatment outcomes. Patient subgroup with higher cortical thickness had higher rate of recurrent seizure. Abstract: Purpose: In the current study, we examined the potential of neuroanatomic measures to cluster patients into different subgroups and established their clinical relevance to post-treatment outcomes. Methods: We included seventy-two children with epilepsy (aged 14–195 months) who were treated with anti-seizure medication alone and 39 healthy participants (aged 36–60 months). High-resolution T1-weighted imaging was performed for all participants, and brain cortical thickness measurements were obtained for 68 cortical regions for each of them. Amongst the patients, data-driven hierarchical cluster analysis was performed using the selected cortical thickness measures as features. The average thickness measures in each of the 68 brain regions were then compared between patient subgroups and healthy controls. Results: Two distinct patient subgroups were identified but were not related to the clinical types. Patients within subgroup 1 ( n  = 56) had a significantly higher rate of recurrent seizure than those in subgroup 2 ( n  = 16) (41.1% vs. 14.3%, p <0.05), while the follow-up time or medication did not differ between them. This finding was further confirmed by a recent follow-up through phone calls. The demographic variables, rate of electroencephalogram abnormalities, or sleep problems did not significantly differ between patient subgroups. Compared with healthy controls, patients in subgroup 1 showed significantly increased cortical thickness in the neocortex, whereas patients in subgroup 2 only showed regional cortical thinning in the right superior temporal gyrus. Conclusion: These findings suggest the potential existence of distinct subgroups of children with epilepsy that were especially relevant to the differential patterns of post-treatment outcomes, with regional cortical thinning in the temporal regions relative to controls predicting lower risk of recurrent seizure.